Inventarisasi Serangga pada Lahan Pertanian Hortikultura di Kelurahan Sasi Kecamatan Kota Kefamenanu - Maria Marselina Bay; Yunita T. S. Tneup; Gonsianus Pakaenoni (Fakultas Pertanian, Universitas Timor, 2022)
Horticulture is a science that studies the intensive cultivation of plants and products that are used by humans as food, fresheners or flavorings and as an alternative to protecting and protecting plants for the environment. The aims of this research are: to find out what types of insects are found in horticultural plants in Sasi Village, the grouping of insects on horticultural plants in Sasi Village and the influence of environmental conditions on the presence of insects on horticultural plants in Sasi Village. This research was conducted in Horticultural Agricultural Land, Sasi Village, Kefamenanu City District. The method used in this research is the pitfall trap, sweep net and yellow tray method. The results showed that on the horticultural agricultural land of Sasi Village there were 5 types of insects, namely: order Coleoptera, order Diptera, order Hymenoptera, order Ortoptera, order Lepidoptera and 12 insect families, namely: Family Scarabaidae, family Coccinelidae, family Chrysomelidae, family Curculinidae, family Muscidae , family Tephritidae, family Tehrididae, family Eulophidae, family Gryllidae, family Pieridae, family Bombylidae and family Noctuidae, with a total of 237 individuals.